Effect analysis of biomineralization for solidifying desert sands - Linchang Miao; Hengxing Wang; Xiaohao Sun; Linyu Wu; Guangcai Fan (Biogeotechnics)
The sand-dust weather has become an environmental hazard in the world. However, it is still a challenge to control sandstorms and decrease sand-dust weather. The biomineralization technology for solidifying desert sands has been developed as a novel method in recent years. In this study, the wind erosion tests and verification tests of the sand solidification system were conducted via a series of laboratory experiments. The effects of sand barriers, injecting volume and concentration of the biochemical solution in the sandstorm protection were studied. Moreover, a field test of 60,000 square metres was conducted in the solidification area on both sides of the Wuma Highway in the Tengri Desert. The biomineralization technique was used to solidify sand to prevent the wind from blowing quicksand onto the newly built highway and causing accidents. Results demonstrated that the biomineralization sand solidification method had a good solidification ==effect, improved the survival rate, and promoted the growth of plants in the desert. This innovative biomineralization technology is an environmentally responsible technology to control sandstorm disasters.